Social logistics: Rethinking public transport as a regional distributor of goods in rural areas. Chances for the long-term establishment of a sustainable regional logistics approach - Greischel, Eva; Nagy, Emilia; Conrad, Alexander; Schäfer, Martina (Raumforschung und Raumordnung | Spatial Research and Planning, 2024)
This paper presents initial findings on the establishment of a social logistics project in a peripheral rural region in Germany. As part of a real-life laboratory, two services were developed and tested with the aim of improving rural supply: the delivery of regional goods and the return of online orders in cooperation with a regional public transport provider, regional retailers and parcel services. An evaluation team provided support to the project in identifying, monitoring, and documenting the societal impact of the services and promoted impact-oriented project management. The concept of providing services of general interest through social logistics and testing them in a real-world laboratory was based on preliminary work in the region. The results indicate that this approach can promote this type of social logistics in the long term. A social logistics approach does not focus solely on economic aspects but emphasises social and environmental benefits for the region. A real-world laboratory approach enables an environment that promotes open exchange, involvement of different stakeholders and joint problem solving in a reflective, iterative process. This methodological approach enabled the continuation and out-scaling of the service’s core offerings immediately after ending the test phase and is seen as an important prerequisite for establishing a long-term perspective.